2019
DOI: 10.1002/lio2.309
|View full text |Cite
|
Sign up to set email alerts
|

Cervical VEMP tuning changes by Meniere's disease stages

Abstract: Objective To determine if changes in cervical vestibular‐evoked myogenic potential (cVEMP) testing reflect the different stages of cochlea‐saccular hydrops in Meniere's disease (MD). Methods This is a case‐control retrospective series. Forty‐seven patients with unilateral MD by American Academy of Otolaryngology–Head and Neck Surgery diagnostic and staging criteria, and 30 with non‐MD vertigo as control. Meniere patients were further classified based on symptoms at the time of testing as active or stable. Subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 21 publications
0
12
0
1
Order By: Relevance
“…Vestibular sensitivity to motion depends on an end organ’s ratio of mass to stiffness, which sets the resonant frequency. Increased endolymph can be expected to push on vestibular end organs and increase their effective stiffness, which increases the resonant frequency of the saccule as shown by vestibular evoked myogenic potentials 24 27 . The vestibular central nervous system (CNS) has a great capacity to adapt to changes in the peripheral end organs, but over a period of days.…”
Section: Discussionmentioning
confidence: 99%
“…Vestibular sensitivity to motion depends on an end organ’s ratio of mass to stiffness, which sets the resonant frequency. Increased endolymph can be expected to push on vestibular end organs and increase their effective stiffness, which increases the resonant frequency of the saccule as shown by vestibular evoked myogenic potentials 24 27 . The vestibular central nervous system (CNS) has a great capacity to adapt to changes in the peripheral end organs, but over a period of days.…”
Section: Discussionmentioning
confidence: 99%
“…For pointing this problem, the tuning curve method suggested. In this method, amplitude of 500 Hz VEMP compared with that of 1000 Hz in the same ear [33]. The ratio decreased in MD patients (i.e., flattening of the tuning curve occurs because in hydropic Hearing and Vestibular Testing in Menière's Disease DOI: http://dx.doi.org/10.5772/intechopen.107945 ear, endolymphatic tuning shifts to 100 Hz).…”
Section: Cervical Vestibular Evoked Myogenic Potentials (Cvemp)mentioning
confidence: 99%
“…The ratio decreased in MD patients (i.e., flattening of the tuning curve occurs because in hydropic Hearing and Vestibular Testing in Menière's Disease DOI: http://dx.doi.org/10.5772/intechopen.107945 ear, endolymphatic tuning shifts to 100 Hz). They showed that this ratio could be a marker for MD progression because the ratio is high during acute phase and is normal during intermediate stable phase [33]. Of course, the ambiguity is whether we are going to use the test to determine the disorder or to use the test to grade the disorder we already know.…”
Section: Cervical Vestibular Evoked Myogenic Potentials (Cvemp)mentioning
confidence: 99%
“…Because of the fluctuating nature of the disease and unpredictable pattern of audiovestibular damage, only audiometry demonstrating low- to medium-frequency sensorineural hearing loss is considered a diagnostic criterion for definitive MD [ 20 ]. Significant efforts have been made to understand why these patients have vertigo attacks, and numerous studies have been published with regards to vHIT, Cal, electrocochleography and vestibular evoked myogenic potentials in these patients, both during attacks and between attacks [ 22 , 23 , 24 , 25 ].…”
Section: Ménière’s Diseasementioning
confidence: 99%